The Biochemistry, Toxicology, and Uses of the pharmacologically active phytochemicals: Alkaloids, Terpenes, Polyphenols, and Glycosides - Awuchi, Chinaza Godswill (Journal of Food and Pharmaceutical Sciences, 2019)
The research focused on the biochemistry and the medicinal uses of alkaloids, terpenes, polyphenols, and glycosides. Several parts of plants such as bark, root, leaf, stem, etc. are being used to revert abnormalities back to normal, prevent illnesses, or allay symptoms. These plant parts contain bioactive compounds such as terpenes, glycosides, polyphenols, and alkaloids. Alkaloids have a range of pharmacological activities such as antiasthma (e.g. ephedrine), anticancer (e.g. homoharringtonine), antimalarial (e.g. quinine). Other alkaloids possess stimulant (e.g. cocaine, caffeine, theobromine, nicotine) and psychotropic activities (e.g. psilocin), and have been widely used as recreational drugs or in entheogenic rituals. Alkaloids can be toxic too (e.g. tubocurarine, atropine). Although alkaloids act on diverse metabolic systems in humans and animals, they almost uniformly induce a bitter taste. The characteristics and number of the structures of phenol in polyphenols underlie the unique chemical, physical, and biological (metabolic, therapeutic, toxic, etc.) properties of specific members of the class; e.g. ellagitannin and tannic acid. Generally, foods often contain complex mixtures of polyphenols. Several polyphenolic extracts, such as from grape seeds, olive pulp, maritime pine bark, or grape skin, are sold as ingredients for functional foods, cosmetics, and dietary supplements. Terpenoids and terpenes are the primary components of the essential oils of most types of flowers plants. Essential oils are used widely as scents and fragrances in perfumery and also in traditional medicine, such as aromatherapy. Similarly, many plant glycosides are used as medicines Amygdalin and laetrile (a synthetic derivative) were investigated as potential drugs for cancer treatment and were promoted as alternative medicine; nevertheless, they are ineffective and dangerous. Pharmacologically active phytochemicals can have useful applications, as well as safety concerns.